Camel milk and fermented camel milk prevent dextran sulfate sodium-induced ulcerative colitis via the intestinal flora-short-chain fatty acids-mucosal barrier axis in mice - Xu, Weisheng; Dong, Qigeqi; Guo, Qingwen; Li, Ruihua; Abbas, Manzar; Li, Ling; Zhang, Chunlin; Zhao, Guofen (Frontiers in Microbiology, 2025)
IntroductionUlcerative colitis poses a significant threat to human health. Dysbiosis of the gut microbiota and decreased levels of short-chain fatty acids are known contributors to the pathogenesis of ulcerative colitis. While camel milk and fermented camel milk have demonstrated beneficial effects in alleviating intestinal inflammation, the differences in their preventive efficacy against ulcerative colitis and the underlying mechanisms remain unclear. Dextran sulfate sodium can induce ulcerative colitis, at least in part, through activation of the NF-κB/MAPK signaling pathway. This study aims to investigate the differential preventive effects of camel milk and fermented camel milk against dextran sulfate sodium-induced ulcerative colitis in mice and to elucidate the underlying mechanisms mediated by the gut microbiota and short-chain fatty acids.ResultsThrough the study, we found that preemptive intervention with camel milk and fermented camel milk significantly mitigated dextran sulfate sodium-triggered pathological manifestations, including body weight loss (e.g., from 97%in DSS group to 99% in FTC group, p < 0.01), elevated disease activity index (from a peak score of 2.8 to 2.0, p < 0.01), colonic shortening (from 5.8 cm to 6.2 cm, p < 0.01). Both treatments also restored intestinal barrier integrity, increasing the expression of tight junction proteins, and elevated the anti-inflammatory cytokineIL-10 (p < 0.05). Then, it can also regulate the intestinal flora imbalance in mice with ulcerative colitis. Finally, we found that both can also reduce the reduction of short-chain fatty acids in mice with ulcerative colitis (p < 0.05). Notably, the fermented camel milk exhibited superior efficacy compared to the camel milk in mitigating fermented camel milk-induced body weight loss, the decline of IL-10and E-cadherin levels, microbial diversity decreasing, the Bacteroidetes/Firmicutesratio increasing, and the relative abundance of Lachnospiraceae NK4A136 group decreasing in ulcerative colitis mice.DiscussionOur findings demonstrate that preemptive intake of camel milk and fermented camel milk effectively prevents ulcerative colitis by preserving the intestinal barrier, regulating immune responses, and restoring gut microbiota homeostasis and short chain fatty acids production, with fermented camel milk offering enhanced benefits. We hold optimistic prospects for camel milk and fermented camel milk as dietary supplements to prevent ulcerative colitis and stabilize gut microbiota homeostasis.